Perancangan Sistem Informasi Perencanaan dan Pengendalian Persediaan Bahan Baku di PT. X - Pudji Astuti; Mohammad Ali Wafa; Iveline Anne Marie (JURNAL TEKNIK INDUSTRI, 2018)
PT. X is a company engaged in the production of paper pallet packaging for exports. In the production process, PT. X implements Make-To-Order production strategies which would begin to manufacture if the company has received orders from customers. Recently the problems facing by company are the uncertainty lead-time delivery and uncertainty of demand from customer. Both of these issues resulted the ordering of raw materials were unplanned and further caused in delayed delivery of finished products to customers. Furthermore the use of conventional display board currently leads to human error either recording the customer orders or calculating the availability of raw materials.The objective of this research, to solve the problem, proposed decision support system or DSS which will helps the company to schedule procurement of raw material and helps to control raw material availability. Stage of designing the DSS is using the waterfall system development so that the process is done by sequentially developed for each phase of development.The system development process is starting from the system initiation, analysis, design system and implementation. To analyze process, used object-oriented approach which point in the making of models to help analyze and understanding the problem. Results from the study showed that the problems faced by company solved by implementing the safety stock and the procurement scheduling which integrates with early warning sub model, Material Requirement Planning (MRP) sub model and inventory sub model, into a web-based decision support system that can be accessed anywhere, anytime and accurately by authorized user. Safety stocks are used as a backup supply which will be used when the uncertainties of demand occurred. MRP sub model schedules the procurement and calculate raw material requirements based on Bill of Material. Inventory sub model with early warnings system will provide a reminder to the user if the amounts of raw materials available have reached a certain condition so that users can perform further actions to maintain the availability of raw materials.